2022
DOI: 10.1002/jbt.23240
|View full text |Cite
|
Sign up to set email alerts
|

Examination of antimicrobial effect of fluoxetine in experimental sepsis model: An in vivo study

Abstract: Since most infectious diseases can develop into sepsis, it is still a major medical problem. Some in‐vivo studies showed promising properties of fluoxetine in the treatment of infections. This study aims the antimicrobial effect of fluoxetine on the inflammatory process used in the treatment of sepsis‐modeled rats. Besides, to investigate the efficacy of fluoxetine on modifying the antibiotic effect of imipenem in the inflammatory response. An experimental sepsis model was divided into negative control, positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Batista de Andrade Neto et al, 2019;Dos Santos et al, 2020). Recent studies indicate that administration of fluoxetine in an in vitro model of sepsis inhibits the synthesis of interleukin 1 beta (IL-1β), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), myeloperoxidase (MPO) activity, monocyte chemoattractant protein -1 (MCP-1), high sensitivity C-reactive prhs-CRP, procalcitonin (PCT), lactate, and the oxidative stress index (OSI), and di-sulfide levels (Cakir et al, 2022). In a 2019 study, it was confirmed that escitalopram oxalate inhibits the growth of E. coli at a concentration of 45, 15, and 5 mM, while Bacillus subtilis is not inhibited (Valipour et al, 2019).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Batista de Andrade Neto et al, 2019;Dos Santos et al, 2020). Recent studies indicate that administration of fluoxetine in an in vitro model of sepsis inhibits the synthesis of interleukin 1 beta (IL-1β), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), myeloperoxidase (MPO) activity, monocyte chemoattractant protein -1 (MCP-1), high sensitivity C-reactive prhs-CRP, procalcitonin (PCT), lactate, and the oxidative stress index (OSI), and di-sulfide levels (Cakir et al, 2022). In a 2019 study, it was confirmed that escitalopram oxalate inhibits the growth of E. coli at a concentration of 45, 15, and 5 mM, while Bacillus subtilis is not inhibited (Valipour et al, 2019).…”
Section: Antidepressantsmentioning
confidence: 99%